PERAN PRODUCT KNOWLEDGE CASHIER PADA PELAYANAN P.O.S DELICA TERHADAP CUSTOMER SATISFACTION PT AEON INDONESIA SENTUL - Jasmine Fairuz Syahda (Business Management and Entrepreneurship Journal, 2021)
Currently, modern retail business continues to grow, and all modern retail businesses must do their best in their services and services. Customer satisfaction is a valuable asset for retail companies. The quality of human resources must also be considered, especially cashiers. The cashier is the part of retail that deals directly with customers. Employee knowledge, and of course the cashier is needed to meet and answer customer questions and make customers feel satisfied. If customer satisfaction has been achieved, then the company will be easy to survive in the business competition that occurs in this era. The purpose of the observation was to determine how important product knowledge is for the cashier and all obstacles encountered in the application of product knowledge in area P.O.S cashier delica PT AEON Indonesia. The method used is, observation method that is down directly to the area P.O.S cashier PT Aeon Indonesia, Sentul City to observe the application of product knowledge at the cashier. The next method is the study of literature, which is assisted by reading journals, literature, books, and articles. Product knowledge is a soft skill that must be owned by all staff, if it is not trained will cause customer complaints. In overcoming this, PT Aeon Indonesia, especially the cashier section, can conduct training for its employees in the aspect of product knowledge, and training must be carried out regularly so that the results are maximized.Keywords: Product Knowledge, Delica, Customer Satisfaction, Cashier